Functional Ultrasound Imaging of Auditory Responses in Comatose Patients - Zihao Chen; Na Li; Caihua Xi; Jiaru He; Jiejun Zhu; Gang Wu; Jinzhao Xia; Chunlong Fei; Lei Sun; Hongzhi Xu; Zhihai Qiu (Research)
Bedside monitoring of brain function in severely brain-injured patients remains a critical clinical challenge. We demonstrate the translational potential of functional ultrasound (fUS) imaging for this purpose. In 6 comatose patients (Glasgow coma scale ≤ 8) with cranial windows after decompressive craniectomy, we used a 7.8-MHz transducer optimized for cortical depths of 1.5 to 4 cm to perform real-time fUS during auditory stimulation. We observed task-related increases in regional cerebral blood flow (rCBF) in relevant brain regions (P < 0.001, t test), which correlated with subsequent neurological recovery at 9-month follow-up. These findings establish fUS as a sensitive and portable tool for bedside brain function assessment, offering potential for improved prognostication, treatment guidance, and development of targeted rehabilitative strategies.